(untitled) (Modern education and development, 2024)
Ushbu maqola yerga ishlov berishda samaradorligni oshirish uchun innovatsion texnologiyalar va qishloq xo’jaligi mashinalaridan foydalanish uchun ma’lumotlar berilgan. This article provides information on the use of innovative technologies and agricultural machinery to improve efficiency in land processing.